Examining the Concept of Impact as a Tripartite Emergence: A Contribution for the Analy-sis of Citizen Coexistence - Téllez Aroca, Celio Arnulfo; Castañeda Barón, Blanca Lilia; Guzmán Pinzón, Claudia Alexandra; Gantiva Rocha, Jesús Aníbal (Rastros Rostros, 2014)
This article presents a proposal to widen the components and implications of the concept of “impact”, to reveal new aspects and scope for both its characterization and measurement, as well as offering various options for interpreting it. As a starting point, the concept of impactus is examined in studies from various academic centers, and its aspects are then inferred in order to contrast and complement them from a sociocybernetics perspective. Through this exercise, it was possible to see the existence (in the reference works consulted) of clear, homogenizing and exclusive trends in the three independent processes of human beings (acting, feeling and acting), that contrast with impact as an emergence. The challenge in making sense of this from the proportionality of human potential is to discover new ways of approaching the world of signs of influence in post-graduate university programs, individuals, society, and the world.